Os impactos das tecnologias digitais de comunicação nos relacionamentos afetivos: os sentidos do controle - Albuquerque, Sabrina Alvares Baptista de (2020)
The main goals of this research are to understand how the use of technology with the intention of controlling a partner has impacted current relationships and observe what is behind this desire for control. The methodology is based on Heideggerian thinking because it offers important elements that clarify the participants’ experience and subsidises the understanding of the control theme and also increases understanding of its existence today. Respecting ethical care based on Resolution CNS MS 466/2012, supplemented by Resolution CNS MS 510/2016, the method was divided into three groups. In the first one, an invitation to take part in the research was available, combined with a structured questionnaire. The main objective was to identify participants who claimed to have a habit of checking their partner's social media with or without their permission. For the second group, six participants were selected. They met the criteria and agreed to participate in the third group - an open interview with two guiding questions. The participants were five women and one man, aged 24 to 50, in relationships between 2 and 25 years. After transcribing and reading the material and analysing the results, we highlighted the themes that present the meanings behind the need to have control over partners. These were organised into five central themes: 1. Perception of the act of verifying the partner’s social network; 2. Reasons for such action; 3. What sustains the action; 4. Self-inflicted suffering; 5. The vision of the possibility of controlling the other one. The analysis showed that participants aimed to escape the anguish of unpredictability by seeking control. In fear of being betrayed, deceived or the breakup of the relationship, the interviewees try to demand transparency and supervision. However, instead of relief, such a search brought significant suffering to most participants. Despite seeking control, it is important to highlight that five in six interviewees clearly stated that it is not possible to exercise control over their partner. However they do not do so because they accept and understand the partner’s free will or the unpredictability of life, but because they realize that it is impossible to watch anyone all the time personally or digitally. It is the feeling of self-doubt and the habit of comparing oneself to others that contributes to the difficulty in dealing with unpredictability, and which appeared most significantly. For its relevance, this study is indicated for the improvement of clinical management; and important reflections are also proposed to the general public. New research themes are also suggested as they seek to understand the impacts on those who are "the target" by the desire for control. This work was carried out with the support of the Higher Education Personnel Improvement Coordination - Brazil (Capes) - Financing Code 88887.169519/2018-00